2016
DOI: 10.1111/jvh.12628
|View full text |Cite
|
Sign up to set email alerts
|

Higher incidence of HCV in females compared to males who inject drugs: A systematic review and meta‐analysis

Abstract: Women who inject drugs have been shown to have higher incidence of HIV and risk behaviors than men, but there are conflicting reports about hepatitis C virus (HCV) incidence. We systematically reviewed the literature to examine the female to male (F:M) HCV incidence in female and male persons who inject drugs (PWID), and also to explore the heterogeneity (i.e., methodological diversity) in these differences. We searched PubMed and EMBASE for studies published between 1989 to March 2015 for research that report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 48 publications
1
29
1
5
Order By: Relevance
“…The primary risk factor for HCV infection in PWID is using a needle or syringe, which has been already used by another user (sharing syringes) (13,15,(19)(20)(21)(22)(23). Sharing other injection equipments (eg, cookers, swabs, tourniquets, and mixing water) is also common among PWID (24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…The primary risk factor for HCV infection in PWID is using a needle or syringe, which has been already used by another user (sharing syringes) (13,15,(19)(20)(21)(22)(23). Sharing other injection equipments (eg, cookers, swabs, tourniquets, and mixing water) is also common among PWID (24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…The female PWID in the current study tested significantly more positive on HCV antibodies than the male respondents. A systematic review and meta-analysis of 28 studies published globally found an overall higher risk of HCV infection of 36% for female PWID compared with male PWID [35]. Since the profile of these women in the current study did not vary significantly from men for other variables, it is necessary to study the behavioral or structural factors contributing to sex-related differences more in detail in future research.…”
Section: Discussionmentioning
confidence: 78%
“…The female PWID in the current study tested significantly more positive on HCV antibodies than the male respondents. A systematic review and meta-analysis of 28 studies published globally found an overall higher risk of HCV infection of 36% for female PWID compared to male PWID [35]. Since the profile of these women in the current study did not vary significantly from men for other variables, it is necessary to study the behavioral or structural factors contributing to sex related differences more in detail in future research.…”
Section: Discussionmentioning
confidence: 78%